2021
DOI: 10.1002/alr.22782
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and convergent validity of the chronic rhinosinusitis patient‐reported outcome (CRS‐PRO) measure in CRS patients undergoing endoscopic sinus surgery

Abstract: Background:The chronic rhinosinusitis patient-reported outcome (CRS-PRO) measure is a 12-item measure with previously demonstrated validity in chronic rhinosinusitis (CRS) patients receiving medical therapy. This study establishes the factor structure, responsiveness, and convergent validity of the CRS-PRO following endoscopic sinus surgery (ESS). Methods: Northwestern CRS Subject Registry patients had pre-ESS, 3-month (n = 111; CRS without nasal polyps [CRSsNP] = 60, CRS with nasal polyps [CRSwNP] = 51), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…These were acquired before ESS and at 6‐ to 12‐month post‐ESS follow‐up. Scores for each individual question were recorded and total score as well as each subdomain score were recorded for each individual survey 23,24 . For all these measures, an increase in disease severity is indicated by a higher score (SNOT‐22: range, 0‐110; CRS‐PRO: range, 0‐48).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These were acquired before ESS and at 6‐ to 12‐month post‐ESS follow‐up. Scores for each individual question were recorded and total score as well as each subdomain score were recorded for each individual survey 23,24 . For all these measures, an increase in disease severity is indicated by a higher score (SNOT‐22: range, 0‐110; CRS‐PRO: range, 0‐48).…”
Section: Methodsmentioning
confidence: 99%
“…These include the rhinologic, extranasal, ear/facial, psychologic, and sleep disturbance subdomains 24 . Similarly, a recent factor analysis of the CRS‐PRO revealed 3 distinct subdomains: rhinopsychologic, facial discomfort, and cough 23 . These symptom domains are aggregations of individual questions whose responses track with each other and may reflect sources of variance on a PROM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It differs from the SNOT‐22 primarily in that it was developed with extensive input from patients who had CRS defined using current definitions of CRS including its two major phenotypes. At 12 items, it is also more concise than the SNOT‐22 21–23 . Pre‐ESS CRS‐PRO was completed for 36 (69%) patients and pre‐ESS SNOT‐22 was completed for 42 (81%) patients.…”
Section: Methodsmentioning
confidence: 99%
“…Senior et al 46 demonstrated that an exhalation delivery system with fluticasone improved symptoms for patients with CRS irrespective of whether patients used conventional delivery nasal steroid sprays previously. Lin et al 47 showed that the Chronic Rhinosinusitis Patient-Reported Outcome survey is a valid and responsive instrument for assessing QoL changes in patients undergoing sinus surgery. Little et al 48 prospectively validated the Sinus Control Test (SCT) in a multicenter cohort of 218 patients after ESS.…”
Section: Novel Technologies and Outcome Measuresmentioning
confidence: 99%